Improved version of the digital map of natural cover of the first edition cartographic sheets of Costa Rica scale 1:25,000 - Calvo-Alvarado, Julio (2024)
Land cover maps are crucial for understanding land use change and for conserving and wisely managing natural resources. However, detailed digital mapping information was only available in Costa Rica after the introduction of LANSAT images and the use of Geographic Information Systems (GIS) in the 1980s. Therefore, retrieving information from historical cartographic sheets is crucial to providing a better historical baseline for the Nicoya Peninsula of Costa Rica. This article explains the process of converting and improving the land cover map from the first edition of the cartographic sheets of Costa Rica into digital format. These sheets were initially published in print by the National Geographic Institute (IGN) at a scale of 1:25,000, based on aerial photographs taken in 1945. These cartographic sheets contain valuable information about the land covers of forests, wetlands, mangroves, salt pans, and water bodies. Hence, the primary objective of this project was to create a single and improved layer of natural land covers in digital format, which will be free and open access to the public through the National Territorial Information System (SNIT) platform of the National Geographic Institute of Costa Rica.